IMAPACT OF CULTURAL HERITAGE TOURISM-AN OVERVIEW - Shankar, S. (IJRDO -Journal of Computer Science Engineering, 2015)
In general, the world’s leading category ofinternational trade, tourism, is increasinglyoffering a range of cultural heritageproducts, from visiting monuments todiscovering unique ways of life as supplyfor increasing cultural and heritage tourismdemand. UNESCO defines culture tourismas “to create a discerning type of tourismthat takes account of other people’scultures” . Indeed culture and heritagetourism has been gaining importancerecently not only for its’ economic gains butdue to more sustainable approaches. Asrural and regional economies go throughdifficult times of change, it may seem tosome local communities that heritage canhelp in terms of economical gains. Whenwhat is old and valued in the community canno longer serve its original function, surelyit can still attract funding and tourism as apart of cultural heritage. It is a well knownfact that a natural link exists betweencultural heritage tourism and regionaldevelopment. Regional development is akey factor which contributes to economicwelfare of the host country. Thedevelopment and application of a systemassessing the tourism potential of culturaland heritage assets including cultural,physical, product and experiential values isvital for the sustainability of the tourismattractions. The purpose of this paper is todetermine whether there is a link betweencultural and heritage tourism and regionaldevelopment.